Adolescents with obesity treated with exenatide maintain endogenous GLP-1, reduce DPP-4, and improve glycemic control - Stenlid, Rasmus; Cerenius, Sara Y.; Wen, Quan; Aydin, Banu Küçükemre; Manell, Hannes; Chowdhury, Azazul; Kristinsson, Hjalti; Ciba, Iris; Gjessing, Erik S.; Mörwald, Katharina; Gomahr, Julian; Heu, Verena; et al. (Frontiers in Endocrinology, 2023)
Background GLP-1 receptor agonists (GLP-1RA) are increasingly used to treat adolescent obesity. However, the effect on endogenous GLP-1 secretory patterns following treatment in adolescents is unknown. The GLP-1RA exenatide was shown to significantly lower BMI and 2-hour glucose in adolescents with obesity, in the placebo-controlled, randomized controlled trial Combat-JUDO. The aim of this study was to evaluate effects of weekly injections of 2 mg exenatide extended release on secretory patterns of endogenous hormones during OGTT. Subjects and Measurements This study was a pre-planned sub-study of the Combat-JUDO trial, set at the Pediatric clinic at Uppsala University Hospital, Sweden and Paracelsus Medical University, Austria. 44 adolescents with obesity were included and randomized 1:1 to treatment:placebo. 19 patients in the treatment group and 18 in the placebo group completed the trial. Before and after treatment, GLP-1, glucose, insulin, glucagon and glicentin levels were measured during OGTT; DPP-4 and proinsulin were measured at fasting. A per-protocol approach was used in the analyses. Results Exenatide treatment did not affect GLP-1 levels during OGTT. Treatment significantly lowered DPP-4, proinsulin and the proinsulin-to-insulin ratio at fasting, increased glicentin levels but did not affect insulin, C-peptide or glucagon levels during OGTT. Conclusion Weekly s.c. injections with 2 mg of exenatide maintains endogenous total GLP-1 levels and lowers circulating DPP-4 levels. This adds an argument in favor of using exenatide in the treatment of pediatric obesity. Clinical trial registration clinicaltrials.gov, identifier NCT02794402